The impact of surface currents and sea level on the wave field evolution during St. Jude storm in the eastern Baltic Sea - Marili Viitak; Ilja Maljutenko; Victor Alari; Ülo Suursaar; Sander Rikka; Priidik Lagemaa (Oceanologia, 2016)
A third generation numerical wave model SWAN (Simulating WAves Nearshore) was applied to study the spatio-temporal effect of surface currents and sea level height on significant wave height; and to describe the mechanisms responsible for wave–current interaction in the eastern Baltic Sea. Simulation results were validated by comparison with in situ wave measurements in deep and shallow water, carried out using the directional wave buoy and RDCP respectively, and with TerraSAR-X imagery. A hindcast period from 23 to 31 October 2013 included both a period of calm to moderate weather conditions and a severe North-European windstorm called St. Jude. The prevailing wind directions were southerly to westerly. Four simulations with SWAN were made: a control run with dynamical forcing by wind only; and simulations with additional inputs of surface currents and sea level, both separately and combined. A clear effect of surface currents and sea level on the wave field evolution was found. It manifested itself as an increase or decrease of significant wave height of up to 20%. The strength of the interaction was influenced by the propagation directions of waves and surface currents and the severity of weather conditions. An increase in the wave height was mostly seen in shallower waters and in areas where waves and surface currents were propagating in opposite directions. In deeper parts of the eastern Baltic Sea and in case of waves and surface currents propagating in the same direction a decrease occurred.